FACTORS RELATED TO BEHAVIOR OF USING PERSONAL PROTECTIVE EQUIPMENT ON WORKERS AT GONDORUKEM AND TURPENTINE FACTORIES PONOROGO - Ahmad Hendriansyah; Sisca Mayang Phuspa; Ani Asriani Basri; Ratih Andhika Akbar Rahma (Journal of Industrial Hygiene and Occupational Health, 2019)
Workers need Personal Protective Equipment (PPE) when working to minimize the amount of risk and hazard exposure from work accidents. The behavior of the use of PPE is influenced by predisposing, supporting and reinforcing factors. The purpose of this study was to determine the factors associated with the behavior of PPE use in the Sukun Gondorukem and Turpentine Factory (PGT), Ponorogo. This study uses a cross-sectional study design. The method of taking data with a purposive sampling technique that is workers in PGT Sukun Ponorogo, amounting to 30 respondents. The dependent variable in this study is the behavior of using PPE. The independent variables of research are knowledge, attitude, training, availability of PPE, communication, motivation, supervision, punishment and rewards. Research instruments using questionnaires and check lists. This research shows knowledge variables (p-value 0,407), attitude (p-value 0,195), training (p-value 0,064), PPE availability (p-value 0,267), and motivation (p-value 0,267) not related to behavior using APD. While the communication variables (p-value 0.011), supervision (p-value 0.007), punishment (p-value 0.029) and rewards (p-value 0.003) were proven statistically related to behavior using PPE. Keywords : PPE, predisposing factors, supporting factors, reinforcing factors, PPE usage behavior